PEMBANGUNAN SOSIAL, KESEJAHTERAAN SOSIAL, DAN PEKERJAAN SOSIAL - Witono, Toton (Quantum: Jurnal Ilmiah Kesejahteraan Sosial, 2020)
What are social welfare, social development, and social work? How are they related each other? This paper is an effort to answer these questions by clarifying these concepts and their short history and also examining their relationships. Social welfare is a precondition to make the national goal come true. The government’s political ideology will determine the approach in achieving social welfare that underlie programs and policies making. In general, there are two major views by which social welfare is pursued, ie. residual and institutional. Amidst the two contradictory approaches, social development emerged as the alternative discourse. Social development is an in-between-approach that is in line with both residual and institutional view. Actually, social work is also an approach as well as one of professional groups in social welfare. Nevertheless, this profession can be adaptable to implement the mainstream approaches and is compatible with social development.